Implications of E‑Mobility from a User Behavior Perspective Regarding Traffic, Environment and Space - Döring, Thomas; Aigner-Walder, Birgit (Raumforschung und Raumordnung | Spatial Research and Planning, 2017)
For the individual acceptance and social dissemination of technological innovations like e‑Mobility in an appropriate manner the decision behaviour of potential users should be taken into account. In consideration of this the paper provides an overview of relevant determinants of individual willingness to substitute between conventional propulsion technologies and electrical drive engineering in the field of individual motor car traffic in terms of subjective opportunity costs and other important behaviouristic effects. Based on these insights some significant implications of e‑Mobility regarding future trends in traffic, important environmental effects as well as the spread of e‑Mobility in urban and rural areas will be derived.